Pengaruh Model Pembelajaran Koopertif Tipe Quick On The Draw Terhadap Hasil Belajar Matematika Siswa - Nurlinda Nurlinda (Tautologi: Journal of Mathematics Education, 2023)
The purpose of this study was to determine that the Quick On The Draw type of cooperative learning model had a positive effect on the mathematics learning outcomes of eighth grade students of UPTD SMP Negeri 3 Parepare. This type of research is a quasi-experimental study without a control class conducted in one-group pretest and posttest design. The variables studied in this study were the mathematics learning outcomes of class VIII UPTD SMP Negei 3 Parepare as the dependent variable and learning using the Quick On The Draw cooperative learning model as the independent variable. The population of this study were students of class VIII UPTD SMP Negeri 3 Parepare in the odd semester of the 2022/2023 academic year. The sample of this study was class VIII.3 students, totaling 28 people who were obtained using cluster random sampling technique.The research data were obtained using research instruments in the form of mathematics learning outcomes tests and student activity observation sheets. Based on descriptive statistical analysis, the average value of the pretest results was 51.52 and the posttest was 83.1, the average percentage of student activity was 68.92, and inferential using one sample t-test obtained a significant value of p = 0.00 < α = 0.05, this means that H0 is rejected and H1 is accepted. So it can be concluded that the Quick On The Draw type of cooperative learning model has a positive effect on mathematics learning outcomes for class VIII UPTD SMP Negeri 3 Parepare students.